PENGARUH NILAI TUKAR DAN VOLUME PERDAGANGAN SAHAM TERHADAP RETURN SAHAM PADA INDEKS LQ45 TAHUN 2022-2024 - Saifudin, Muhamad; Kurniasari, Rani; Agustina, Teni (Jurnal Riset Terapan Akuntansi, 2025)
This study aims to prove the effect of exchange rates and stock trading volume on stock returns in companies incorporated in the LQ45 index on the Indonesia Stock Exchange (BEI) in 2022-2024. The type of research conducted uses statistical quantitative methods. The research population includes companies incorporated in the LQ45 index as many as 45 companies. The sampling technique used purposive sampling method so that 25 companies were obtained that met the required criteria and the number of data observations processed was 75 data samples. The analysis technique used to test the hypothesis is multiple linear regression analysis. The results showed that the exchange rate has a negative and significant effect on stock returns which explains when the rupiah weakens against the United States dollar causing stock returns to decline. While the value of stock trading volume has a positive and significant effect on stock returns which explains when an increase in stock trading activity tends to encourage an increase in stock returns. And both simultaneously have a significant effect on stock returns even though the contribution of simultaneous influence is only 21.3% and the remaining 78.7% is influenced by other variables outside the scope of the study. This finding implies that investors and capital market players need to include the analysis of macroeconomic factors such as exchange rates and market activity (trading volume) as a crucial part of the investment decision-making strategy in liquid stocks. Keywords: Exchange Rate, Stock Trading Volume, Stock Return